First UHPLC‐MS/MS method coupled with automated online SPE for quantification both of tacrolimus and everolimus in peripheral blood mononuclear cells and its application on samples from co‐treated pediatric patients. (March 2017) - Pensi, D.; De Nicolò, A.; Pinon, M.; Pisciotta, C.; Calvo, P. L.; Nonnato, A.; Romagnoli, R.; Tandoi, F.; Di Perri, G.; D'Avolio, A.
Abstract : Immunosuppressant drugs used in solid organ transplant are characterized by a narrow therapeutic index, potential drug interactions and significant inter‐ and intra‐patient variability. For these, therapeutic drug monitoring is used to optimize the immunosuppressive treatment, prevent rejection and avoid toxicities. Monitoring immunosuppressant drugs in peripheral blood mononuclear cells (PBMCs) instead of from whole blood represents a substantial improvement providing more reliable information about exposure at the active site. In this perspective special feature, Pr. Antonio D'Avolio and colleagues present a novel validated UHPLC‐MS/MS approach coupled with an automated on‐line SPE platform for the rapid, sensitive, specific and reliable quantification of immunosuppressant drugs in human PBMCs applied to "real‐life" samples from pediatric patients undergoing liver transplantation. Dr. D'Avolio is associate professor of pharmacology and heads the Clinical Pharmacology and Pharmacogenetics Laboratory in the Department of Medical Sciences at the University of Torino (Italy). His research interests are centered on the development of analytical methods and diagnostic kits for the dosage of molecules in biological and non‐biological samples.